THE ORIGIN OF MINANG KABAUNESE SHOWN ON WEDDING CEREMONY VIDEO OF PASAMBAHAN MAANTA MARAPULAI PRODUCED BY ELTA RECORD BUKITTINGGI - YENI AFRIYENI (Journal of English Language and Education, 2017)
This study aims to explain the origin of Minangkabau ancestors in Pasambhan Maanta Marapulai Speech produced by ELTA Record Bukittinggi. This study discusses the origin of Minangkabau ancestors found in the video based on myth. In the preparation of this study researchers used descriptive qualitative methods, which is a method that examines an object by explaining the object. Researchers get supporting data from several books that is literature books, bukujurnal, and other books related to this thesis. In analyzing, the researcher explains the implicit meanings contained in the Maanta Marapulate Extended Speech by both the bridegroom and the bridegroom. The results of this study stated that the ancestors of the Minangkabau people came from the third son of Sultan Iskandar Zulkarnain named Maharaja Diraja, Maharaja Diraja sailed through the Indian Ocean and found an island to the west of Sumatra Island. The island is called Perca Island. Or known also by the name Minangkabau, from there Maharaja Diraja see Mount Merapi then Maharaja Royal along with his entourage went to the top of the Mountain. There they first built the Village, the first village named Siligundi Nan Baselo in Pariangan Padang Panjang. Based on the analysis of the story of the origin of Minangkabau ancestors found in the video Maanta Marapulai Supplement, the researchers concluded that the story is a mythical story.